Study Abroad Fever Among Chinese Students - Qiang, Zha (International Higher Education, 2012)
The numbers of Chinese students choosing to study abroad continues to increase. This article discusses some of the factors creating this demand, and argues that it will continue. One of the main groups are undergraduates who are going abroad for study.